2010
DOI: 10.1007/s12262-010-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic liver abscess: presentation and complications

Abstract: Background Amoebic liver abscess (ALA) is the most common infl ammatory space occupying lesion of the liver. It has a highly variable presentation causing diagnostic diffi culties. Untreated, complicated ALA has high morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
57
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 16 publications
21
57
2
Order By: Relevance
“…Fever, abdominal pain and hepatomegaly were presenting complaints in majority of the patients with amoebic liver abscess comparable to study by Mukhopadhyay M. et al 6 Most common complications other than ruptured liver abscess was pleural effusion which is comparable to study conducted by Mukhopadhyay M. et al…”
Section: Discussionsupporting
confidence: 87%
“…Fever, abdominal pain and hepatomegaly were presenting complaints in majority of the patients with amoebic liver abscess comparable to study by Mukhopadhyay M. et al 6 Most common complications other than ruptured liver abscess was pleural effusion which is comparable to study conducted by Mukhopadhyay M. et al…”
Section: Discussionsupporting
confidence: 87%
“…8 Siddiqui et al reported that according to USG report 70% patients were having single abscess and the rest 30% had multiple abscesses. 6 This pattern of involvement has also been reported in previous series on ALA by Sharma et al, Mukhopadhyay et al and Ghosh et al [10][11][12] In present study, chest X-ray abnormality was more in PLA (50%) compared to ALA group (35.8%). Reports of Choudhary et al reported that chest X-ray finding were abnormal in 39% of cases and was comparable to present study findings.…”
Section: Discussionsupporting
confidence: 89%
“…The reported incidence of complications of amoebic liver abscesses vary from 20%-35% in earlier and 12%-20% in more recent series [3]. Most common complications are related to rupture of the abscess into an organ or adjacent space.…”
Section: Discussionmentioning
confidence: 97%